Biochemical Characterization of Novel GH6 Endoglucanase from Myxococcus sp. B6-1 and Its Effects on Agricultural Straws Saccharification - Zhen Huang; Guorong Ni; Longhua Dai; Weiqi Zhang; Siting Feng; Fei Wang (Foods, 2023)
Cellulase has been widely used in many industrial fields, such as feed and food industry, because it can hydrolyze cellulose to oligosaccharides with a lower degree of polymerization. Endo-β-1,4-glucanase is a critical speed-limiting cellulase in the saccharification process. In this study, endo-β-1,4-glucanase gene (CelA257) from Myxococcus sp. B6-1 was cloned and expressed in Escherichia coli. CelA257 contained carbohydrate-binding module (CBM) 4-9 and glycosyl hydrolase (GH) family 6 domain that shares 54.7% identity with endoglucanase from Streptomyces halstedii. The recombinant enzyme exhibited optimal activity at pH 6.5 and 50 °C and was stable over a broad pH (6–9.5) range and temperature < 50 °C. CelA257 exhibited broad substrate specificity to barley β-glucan, lichenin, CMC, chitosan, laminarin, avicel, and phosphoric acid swollen cellulose (PASC). CelA257 degraded both cellotetrose (G4) and cellppentaose (G5) to cellobiose (G2) and cellotriose (G3). Adding CelA257 increased the release of reducing sugars in crop straw powers, including wheat straw (0.18 mg/mL), rape straw (0.42 mg/mL), rice straw (0.16 mg/mL), peanut straw (0.16 mg/mL), and corn straw (0.61 mg/mL). This study provides a potential additive in biomass saccharification applications.